Hidden Prenatal Malnutrition in the Rat: Role of ?1- Adrenoceptors on Synaptic Plasticity in the Frontal Cortex - Hernandez-Kunstmann, A (2011)
Moderate reduction in the protein content of the mother s diet (hidden malnutrition) does not alter body and brain weights of rat pups at birth, but leads to dysfunction of neocortical noradrenaline systems together with impaired long-term potentiation and visuo-spatial memory performance. As ?1-adrenoceptors and downstream protein kinase signaling are critically involved in synaptic long-term potentiation and memory formation, we evaluated the ?1-adrenoceptor density and the expression of cyclic-AMP dependent protein kinase, calcium/calmodulin-dependent protein kinase and protein kinase Fyn, in the frontal cortex of prenatally malnourished adult rats. In addition, we also studied if ?1-adrenoceptor activation with the selective ?1 agonist dobutamine could improve deficits of prefrontal cortex long-term potentiation presenting these animals. Prenatally malnourished rats exhibited half of ?1-adrenoceptor binding, together with a 51% and 65% reduction of cyclic AMP-dependent protein kinase ? and calcium/calmodulin-dependent protein kinase ? expression, respectively, as compared with eutrophic animals. Administration of the selective ?1 agonist dobutamine prior to tetanization completely rescued the ability of the prefrontal cortex to develop and maintain long-term potentiation in the malnourished rats. Results suggest that under-expression of neocortical ?1-adrenoceptors and protein kinase signaling in hidden malnourished rats functionally affects the synaptic networks subserving prefrontal cortex long-term potentiation. ?1-Adrenoceptor activation was sufficient to fully recover neocortical plasticity in the PKA- and calcium/calmodulin-dependent protein kinase II-deficient undernourished rats, possibly by producing extra amounts of cAMP and/or by recruiting alternative signaling cascades. © 2011 International Society for Neurochemistry.